Piotra Chmielowskiego koncepcja nauczania i uczenia się literatury (z kulturoznawczego punktu widzenia) = Piotr Chmielowski - the conceptions of teaching and learning literature - Jazownik, Leszek (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author of the paper reconstructs the methodologigal and theoretical foundations of the concepts of teaching and learning literature formulated by the most outstanding theoretician and teacher of the Polish Positivism.
Keywords: Chmielowski, Piotr (1848-1904); dydaktyka literatury; 19 w.